ROSELLE CALYX ETHANOL EXTRACT STIMULATES ORAL MUCOSAL WOUND HEALING - At, Sarwono; Df, Suniarti (International Journal of Applied Pharmaceutics, 2018)
Objective: This study aim to analyze the effect of the roselle calyx ethanol extract on oral mucosal wound healing. Methods: Male Sprague Dawley rats (3Â month, 150Â g) were housed under standard temperature conditions (20â€“22Â°C). Punch biopsy wounds were inflicted on the inferior labial mucosal membrane of rats. All treatments (normal saline; 0.1% triamcinolone acetonide; and 3.75%, 7.5%, and 15% roselle calyx ethanol extract) were applied 2Â times daily. Wounded areas were observed after 8Â days of treatment. The specimen of the wounded area was prepared and microscopic slides were analyzed under a light microscope. Results: The histological features of the groups treated with TA and 7.5% roselle calyx ethanol extract showed a similar formation of the epidermis layer and no lymphocytic infiltration of the lamina propria. Conclusion: The application of 7.5% roselle calyx ethanol extract could stimulate oral mucosal wound healing.